Psikologi Komunikasi dalam Penerapan Nilai-Nilai Keislaman di Keluarga - Nandari Ayu Setiana (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2018)
The purpose of this paper the role Psicologi of Communication in applaying Islamic values at schools is to give a potrait about how the efford of teachers creats a releationship with students in order to make them aware of themselves in order to teach them having high moral value. Psikology of communication could become importand thing in live, especially in psicology of communication study which could be a way of guiding studentsin order to make them behaving nicely based on Islamic guidence. At based, Islamic teaching values could be obatained by students at their schools. Thus, it important for teachers to explaine very weel to students about how to be a very good student which is having akhlaqul qarimah. Communicating prosess at schools actually could be an important lesson for teachers themselves as well because it could make every single activity done nicely by students. Through a good communication pattern, students are able to understand with what is instructed by their teacher